INSTRUCTIONAL LEADERSHIP OF SCHOOL ADMINISTRATORS UNDER BANGKOK METROPOLITAN - Pannakan, Sudaporn; Suthiyamt, Urai (Journal of Graduate School Sakon Nakhon Rajabhat University, 2024)
The purposes of this research were 1) to examine the instructional leadership of school administrators under Bangkok Metropolitian, and 2) to compare the instructional leadership of school administrators under Bangkok Metropolitian, classified by educational background, work experience, and school sizes in the academic year 2023. A survey research methodology was utilized with the sample consisting of 370 teachers working in schools under Bangkok Metropolitian. The sample was categorized using Cohen’s sample size tables. Stratified random sampling and simple random sampling were also used to estimate the proportion of different school sizes. The research instrument was a set of questionnaires designed to gather teachers’ opinions on the instructional leadership of school administrators in schools under Bangkok Metropolitan. The questionnaire was evaluated with the index of item objective congruence (IOC) of 1.00, the difficulty value of 0.93, and the reliability of .955. The statistics for data analysis were mean, standard deviation, t–test, One–way ANOVA, and Scheffe’s multiple comparison method. The findings revealed that: 1. The instructional leadership of school administrators under Bangkok Metropolitian was overall and in each aspect at a high level, which was ranked in descending scores as follows: The highest average ratings were curriculum and instructional management, followed by formulation of vision and developmental direction, and promoting professional development. Evaluation and monitoring received the lowest average rating. 2. The instructional leadership of school administrators under Bangkok Metropolitan, categorized by different educational background, work experience, and school sizes, could be summarized as follows: Overall and in each aspect, there were no significant differences in opinions regarding the instructional leadership of school administrators, except in the evaluation and monitoring aspect, which had the lowest mean score. Teachers from different school sizes reported significant differences in their opinions on the instructional leadership of school administrators at the .05 level of significance.